Novel mutation in Hermansky–Pudlak syndrome type 2 with mild immunological phenotype. (November 2013) - Kurnik, Karin; Bartsch, Ingrid; Maul-Pavicic, Andrea; Ehl, Stephan; Sandrock-Lang, Kirstin; Bidlingmaier, Christoph; Rombach, Nina; Busse, Anja; Belohradsky, Bernd H.; Müller-Höcker, Josef; Aslanidis, Charalampos; Schmitz, Gerd; et al.
<x xml:space="preserve">Abstract</x> Patients with Hermansky–Pudlak syndrome type 2 (HPS2) present with oculocutaneous albinism, nystagmus, prolonged bleeding time, and increased susceptibility to infections. Twelve HPS2 patients with mutations in the β3A-subunit of the cytosolic adaptor-related protein complex 3 (AP3B1, also called HPS2) have been described so far. Here, we report on a patient with oculocutaneous albinism who developed a life-threatening bleeding after tonsillectomy. She presented with moderate neutropenia and reduced granulopoiesis. Analyzing patient's impaired platelet function using electron microscopy and flow cytometry led to the diagnosis of HPS2. Flow cytometric analysis of the patient's platelets showed already elevated CD63 expression on resting platelets with no further increase after thrombin stimulation. Natural killer (NK) cell degranulation was partially impaired but target cell lysis of NK cells and cytotoxic T-lymphocytes (CTLs) were normal and the patient did not develop signs of hemophagocytic syndrome. Molecular genetic analyses revealed a novel 2 bp-deletion (c.3222_3223delTG) in the last exon of AP3B1 causing a frameshift and a prolonged altered protein. The location of the deletion at the very C-terminal end may prevent a complete loss of the HPS2 protein leading to a less pronounced severity of immunodeficiency than in other HPS2 patients.